Western Immunoblotting for Bartonella Endocarditis - Houpikian, Pierre (American Society for Microbiology, 2003)
To differentiate infectious endocarditis (IE) from other Bartonella infections and to identify infecting Bartonella bacteria at the species level on a serological basis, we used Western immunoblotting to test sera from 51 patients with Bartonella IE (of which 27 had previously benefited from species identification by molecular techniques), 11 patients with chronic Bartonella quintana bacteremia, and 10 patients with cat scratch disease. Patients with IE were Western blot positive in 49 of 51 cases, and significant cross-reactivity with three heterologous Bartonella antigens was found in 45 of 49 cases. Sera from bacteremic patients did not react with more than one heterologous antigen, and sera from patients with cat scratch disease gave negative results. Sera reacted only with B. henselae in four cases of IE, including one with a positive PCR result for valve tissue. Western blot and cross-adsorption performed on serum samples from patients with IE (the identity of the causative species having been determined by PCR) were demonstrated to identify efficiently the causative species in all cases. When applied to patients diagnosed on the basis of serological tests only, this technique allowed identification of the causative species in 20 of 22 cases. The results were in accordance with epidemiological features. Six reactive bands of B. quintana (of molecular sizes from 10 to 83 kDa) demonstrated significant association with sera from patients with B. quintana endocarditis. Overall, Western blotting and cross-adsorption made it possible to identify the causative species in 49 of 51 (96%) IE cases.